DYNAMIQUE DE TRANSMISSION DE LA GRIPPE SAISONNIERE A ABIDJAN EN COTE D’IVOIRE - N’gattia Kouabenan Anderson; Coulibaly Daouda; Tiembré Issaka; Kadjo Hervé; Ekra Kouadio Daniel; Dagnan N’cho Simplice (European Scientific Journal, ESJ, 2014)
Introduction: In Côte d'Ivoire, the transmission of influenza viruses and climatological factors that influence it are not yet well elucidated to allow the prediction of epidemics. Objective: This study aims to determine the transmission dynamic of seasonal influenza in Abidjan and factors that influence it. Material and Methods: From a review of surveillance data provided by INHP (National Institute of Public Hygiene) and climatological data provided by SODEXAM (National Weather Service) from 2007 to 2010, the monthly and seasonal proportions of flu cases were compared using the Chi-square test. The Pearson correlation test and simple linear regression were performed to investigate the association between the number of influenza cases and climatological data. Results: The monthly proportions of influenza viruses were the highest observed during May (19.5%), June (14.9%) and October (13.9%). The months of May and June are included in the main rainy season where high 48.4% influenza viruses were isolated. Influenza A viruses predominated during the two rainy seasons. Despite a slight statistically significant association between the number of influenza cases and the weekly rainfall (r = 0.18, β = 0.025). Discussion/Conclusion: These findings should guide the prevention of seasonal influenza in the tropics.